Improving the Quality and Relevance of Education through Digital Technology-Based Planning - Ilham Azhari; Brayen Jordi Forester; Novia Nurhayati; Muhammad Sirozi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to analyze the role of digital technology in improving the quality and relevance of education in the era of digital transformation. Using a literature review method and a descriptive qualitative approach, the study examines recent scholarly works discussing the integration of e-learning platforms, virtual reality (VR), and data analytics in the learning process. The results show that digital technology enables more interactive, personalized, and adaptive learning experiences that cater to students' individual needs. Furthermore, it contributes significantly to the development of 21st-century skills such as digital literacy, creativity, problem-solving, and collaboration. However, the implementation of digital technology in education still faces several challenges, including digital access inequality, infrastructure limitations, and low teacher competency in utilizing technology effectively. The main contribution of this study is to provide a comprehensive overview of the opportunities and challenges associated with digital technology in education, along with strategic recommendations for building an inclusive, high-quality, and future-oriented educational system